COMPARISON OF QTc DURATION ON ELECTROCARDIOGRAM BETWEEN PATIENTS OF LIVER CIRRHOSIS AND NON CIRRHOTIC CONTROLS: ECG Changes in Cirrhosis - Umair, Maj Muhammad; Azam, Malik Nadeem; Omer, Muhammad; Mansoor, Junaid; Khan, Hina; Nadeem, Kukab (Pakistan Armed Forces Medical Journal, 2012)
Objective: To compare the QTc duration on electrocardiogram (ECG) of patients of cirrhosis (hep B and C origin) with non cirrhotic controls.Study Design: Case control study.Place and duration of study: The study was carried out at the Department of Medicine, Military Hospital, Rawalpindi, from 8th Feb 2009 to 8th Aug 2009.Material and Method: After meeting the exclusion and inclusion criteria, 80 cirrhotic patients were enrolled in group-I and equal number of non cirrhotic controls were enrolled in group-II. Three 12 lead ECG recording were taken for each patient, 5 minutes apart, and QTc value was calculated for each ECG and then mean of the three was used for the analysis. A QTc value more than 0.44 seconds was taken as prolonged.Results: The mean QTc interval on electrocardiogram in group-I i.e. cirrhotic was 0.4603 seconds (SD±0.1312) and mean QTc interval on electrocardiogram in group-II i.e. noncirrhotic was 0.407 seconds (SD±0.029). These findings were statistically significant (p value < 0.001).Conclusion: Cirrhotic patients have prolonged QTc interval as compared to noncirrhotic controls.